Sistem Penyediaan Air Minum Kabupaten Manggarai dengan Sistem Zonasi di Desa Bangka Kenda - Utama, Teguh Taruna (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2020)
Water resources in Manggarai Regency are mostly supplied from springs. One of the villages in Manggarai Regency that uses springs is Bangka Kenda Village. Bangka Kenda Village requires drinking water of 10.41 Liters/second. This need for water is the result of drinking water projections in Manggarai Regency in 2037. Pressure values obtained from the results of manual calculations range from 5.63 meters to 93.82 meters. While the simulation results using the EPANET program, the pressure value is at 5.69 meters up to 93.84. The value of the manual calculation pressure with EPANET is not much different so that the pipe diameter selection is appropriate according to plan. The selected pipe is HDPE. The selected pipe diameter is 1.5